Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1029/2004pa001081
|View full text |Cite
|
Sign up to set email alerts
|

On the sedimentological origin of down‐core variations of bulk sedimentary nitrogen isotope ratios

Abstract: The bulk sedimentary nitrogen isotopic composition of two cores from nearby sites on the northern slope of the South China Sea (Site 17940 and Ocean Drilling Program (ODP) Site 1144) differs by up to >2‰ during the last glacial period. Given their close proximity, both core sites are located in the same biogeographic zone and nutrient regime, and it is thus unlikely that this offset is due to a true gradient in surface ocean conditions. In an attempt to resolve this offset, we have investigated the possible ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 54 publications
3
59
1
Order By: Relevance
“…6). Such a positive deviation can be seen elsewhere in previous reports (Altabet, 1988;Brummer et al, 2002;Kienast et al, 2005) due to prolonged oxygen exposure after deposition (Robinsson et al, 2012) associated with sedimentation rate (Pichevin et al, 2007). Although Cowie et al (2009) found an ambiguous relation between contents of sedimentary organic carbon and oxygen in deep water, they also noticed the appearance of maximum organic carbon contents at the lower boundary of ODZs, where oxygen content was relatively higher.…”
Section: Downward Transfer and Transformation Of N Isotopic Signalmentioning
confidence: 66%
“…6). Such a positive deviation can be seen elsewhere in previous reports (Altabet, 1988;Brummer et al, 2002;Kienast et al, 2005) due to prolonged oxygen exposure after deposition (Robinsson et al, 2012) associated with sedimentation rate (Pichevin et al, 2007). Although Cowie et al (2009) found an ambiguous relation between contents of sedimentary organic carbon and oxygen in deep water, they also noticed the appearance of maximum organic carbon contents at the lower boundary of ODZs, where oxygen content was relatively higher.…”
Section: Downward Transfer and Transformation Of N Isotopic Signalmentioning
confidence: 66%
“…These complicated processes that may have led to the unrecognizable patterns of temporal variations of δ 15 N during the last deglaciation have been described previously (Higginson et al, 2003). On the other hand, the terrestrial input from different sources might also affect the δ 15 N record in the SCS (Kienast et al, 2005). By comparison, the relatively simple circulation in the open North Pacific Ocean allows the transmission of the signal across the entire basin from the eastern tropical Pacific (Fig.…”
Section: δ 15 N Records In the South China Seamentioning
confidence: 99%
“…The latter is dominated by clay-bound NH + 4 , and can be significant in areas of high clay input relative to organic matter sedimentation Kienast et al, 2005). Terrestrial organic matter can also be significant in the vicinity of rivers or glacial discharge with high particulate loads (McKay et al, 2004), but tends to be overwhelmed by marine organic matter elsewhere (Altabet, 2006).…”
Section: J-e Tesdal Et Al: Nitrogen Isotopes In Bulk Marine Sedimentmentioning
confidence: 99%
“…IAEA-N1, -N2, NIST 8548 or local air), and some laboratories supplement these with their own sediment standards. The combusted material is dominated by marine organic matter at most locations, although there is significant contamination by clay-bound inorganic (Kienast et al, 2005) and terrigenous nitrogen ) in some locations. Given the known problems with acidification of samples (Brodie et al, 2011), we flagged samples that had been acidified where possible, though acidification is not always reported.…”
Section: Database Descriptionmentioning
confidence: 99%
See 1 more Smart Citation